2012
DOI: 10.1258/phleb.2012.012080
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of individual questions from the venous clinical severity score and the Aberdeen varicose vein questionnaire

Abstract: The majority of the individual questions of the VCSS and AVVQ responded to change. However, the cause of a poor response was multifactorial with statistical dilution playing a significant role. Stratification of patients according to ulceration may allow better comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Spearman's  was used to assessed the correlation between the severity of symptoms and AVVQ outcomes. The study reported improved AVVQ score after 3 weeks and 3 months of follow-up 29,30 .…”
Section: +C: Aberdeen Varicose Vein Questionnairementioning
confidence: 80%
See 4 more Smart Citations
“…Spearman's  was used to assessed the correlation between the severity of symptoms and AVVQ outcomes. The study reported improved AVVQ score after 3 weeks and 3 months of follow-up 29,30 .…”
Section: +C: Aberdeen Varicose Vein Questionnairementioning
confidence: 80%
“…A total of 3787 records were identified; following detailed examination, nine studies [25][26][27][28][29][30][31][32][33] (reporting on 4 PROMs) were included ( All the included studies assessed the psychometric properties and suitability of the suggested PROMs in patients with varicose veins ( Table 3). The studies were prospective in design, and were undertaken in the UK and USA.…”
Section: +A: Resultsmentioning
confidence: 99%
See 3 more Smart Citations